2013
DOI: 10.3109/14647273.2013.806824
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene variants and haplotypes associated with an increased risk of idiopathic recurrent miscarriage

Abstract: We investigated the association of endothelial nitric oxide synthase (NOS3) polymorphisms rs2070744 (-786T> C), 27-bp repeat 4b/4a, rs1799983 (Glu298Asp), rs3918188 (-734C> A), and rs743507 (113G> A) with idiopathic recurrent miscarriage (IRM). This was a case-control study involving women with confirmed IRM (n = 296), and 305 age- and ethnically matched control women. NOS3 rs2070744, rs1799983, rs3918188, and rs743507 genotyping was done by TaqMan assays; NOS3 4b/4a genotyping was done by PCR-ASA. A higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our results agree with Luo et al [29], Parveen et al [31] and Almawi et al [32], that revealed a significant association between the rs1799983 genotype distribution in recurrent miscarriage patients. In these studies, women with recurrent spontaneous abortion had a significantly higher frequency of G/T genotype and lower frequency of the G allele compared to control women.…”
Section: Nos3 Genesupporting
confidence: 93%
“…Our results agree with Luo et al [29], Parveen et al [31] and Almawi et al [32], that revealed a significant association between the rs1799983 genotype distribution in recurrent miscarriage patients. In these studies, women with recurrent spontaneous abortion had a significantly higher frequency of G/T genotype and lower frequency of the G allele compared to control women.…”
Section: Nos3 Genesupporting
confidence: 93%
“…After publishing our previous results which concluded that; TAFI 1040C/T could not be considered as a molecular predictive factor for RSA in Egyptians, we could not find any published research that investigated the role of TAFI whether on the molecular or antigen level in pregnancy nor RSA until the time of preparation of the current work. Both eNOS T‐786C and 27bp VNTR of intron 4 were associated in 10 patients who were negative for other studied genes, similarly Almawi et al , found genetic association study replicated a significant association for eNOS variants and haplotypes with RSA. While Shin et al , could not find such an association among Korean patients.…”
Section: Discussionmentioning
confidence: 72%
“…Another study on Lebanon women suggested that eNOS gene promoter variation (-786T > C) sustained a substantial impact on RPL in their women population. [26]. An investigation on a group of Egyptian women exposed a signi cantly association between RPL and this variant [27].…”
Section: Discussionmentioning
confidence: 99%